PVP (Polyvinyl Pyrrolidone) coated Cu-based electro-catalytic material, preparation method thereof and electrode for electro-catalytic reduction of carbon dioxide
The valence state of copper-based catalytic materials is regulated through PVP coating technology, and the problem of insufficient stability and C2 product selectivity in electrocatalytic carbon dioxide reduction is solved, achieving efficient C2 product generation and material stability improvement.
Patent Information
- Application Number
- CN202411404668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing copper-based materials are difficult to maintain a stable intermediate valence state during electrocatalytic carbon dioxide reduction, resulting in low selectivity and Faraday efficiency of C2 products and excessive hydrogen in the competitive reaction product.
By introducing PVP coating technology, the valence state of copper-based catalytic materials is regulated, the two are controlled between monovalent copper and divalent copper, the selectivity of C2 products is improved, and the divalent copper ions are reduced by potassium borohydride solution are prepared to prepare nanosheets A copper-based catalytic material with a shape structure that enhances material stability.
It significantly improves the selectivity and Faraday efficiency of C2 products, improves the stability of the material, enhances the generation of C2 products such as ethylene and ethanol, and reduces the generation of hydrogen.
Smart Images

Figure HDA0005076838980000011 
Figure HDA0005076838980000021 
Figure HDA0005076838980000022
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a PVP-coated Cu-based electrocatalytic material, a preparation method thereof, and an electrode for electrocatalytic carbon dioxide reduction. Background Art
[0002] At present, the world's energy relies on fossil fuels, and the scarcity of fossil fuels has caused environmental problems and energy crises, which has caused great controversy. The exponential growth of the world's population has led to an increase in global energy consumption, and fossil fuels remain the main source to meet energy needs. However, the continued use of fossil fuels will produce a large amount of anthropogenic greenhouse gases. Renewable energy replacing fossil fuels can alleviate the environmental and energy crises to a certain extent, while modern renewable energy including hydropower, wind power, bioenergy, geothermal energy / ocean energy / solar energy accounted for only 11.2% of global energy consumption in 2019. Today, mitigating the emission of carbon dioxide in the atmosphere has become a key challenge facing the scientific community.
[0003] Electrocatalytic reduction of CO2 has attracted widespread attention as an efficient and convenient way to convert CO2. The products of electrocatalytic reduction of CO2 are rich, including carbon monoxide (CO), methane (CH4), formic acid (HCOOH), ethylene (C2H4), ethanol (C2H5OH), etc. C1 products such as carbon monoxide, methane, and formic acid have a Faraday efficiency of nearly 90% because they require fewer electrons in the reduction process and have a relatively simple reaction path. The generation of C2 products requires further CC coupling on the surface of the catalytic material, the reaction path is long, and the multi-electron process often requires a higher overpotential. Therefore, the Faraday efficiency of C2 products is often low and the product selectivity is poor. Among many catalytic materials, copper-based materials have moderate adsorption strength for *CO reaction intermediates, which is more conducive to CC coupling and easier to carry out. Therefore, copper has unparalleled advantages over other metal catalysts in producing C2 products.
[0004] The performance of directly using bulk polycrystalline copper as the working electrode in the electrocatalytic reduction of CO2 is poor. The yield of hydrogen, the competitive reaction product, is too high, and the carbon-containing products are mostly carbon monoxide, with less C2 products. Current research has shown that the factors that affect the selectivity of CO2 reduction products in copper-based materials include the size, morphology, crystal grain boundaries, element valence, etc. of the material, among which the zero-valent (Cu 0 ), divalent (Cu 2+ ) Intermediate valence copper (Cu + ) is more conducive to the formation of C2 products, while copper oxide (CuO) is more conducive to the production of methane. However, intermediate copper ions are difficult to prepare and it is difficult to maintain a stable intermediate valence state during the electrochemical reduction process. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a PVP-coated Cu-based electrocatalytic material, a preparation method thereof, and an electrode for electrocatalytic carbon dioxide reduction. The PVP-coated Cu-based electrocatalytic material prepared by the method can improve the selectivity of C2 products and improve the stability of the material.
[0006] The present invention provides a method for preparing a PVP-coated Cu-based electrocatalytic material, comprising the following steps:
[0007] mixing cupric chloride dihydrate, polyvinyl pyrrolidone (PVP) and dimethylformamide to obtain a mixed solution;
[0008] Under a protective atmosphere, a potassium borohydride solution is added dropwise to the mixed solution under stirring to generate a precipitate, which is then centrifuged and dried to obtain a PVP-coated Cu-based electrocatalytic material.
[0009] The present invention introduces PVP (polyvinyl pyrrolidone), which has the advantages of low price and wide source. Divalent copper ions are reduced by potassium borohydride solution to successfully prepare a cross-linked nano-sheet structure copper-based catalytic material. A sufficient amount of high molecular polymer PVP is introduced during the reduction process to coat the nano-sheet structure copper, and at the same time, the valence change of the divalent copper ions during the reduction process is effectively regulated to control it between monovalent copper and divalent copper, so that it is more conducive to the generation of C2 products.
[0010] In the present invention, the mass of cupric chloride dihydrate, the mass of polyvinyl pyrrolidone and the volume ratio of dimethylformamide are 0.34 g: (0.18-0.22) g: (14-16) mL. The present invention controls the valence state of the copper-based catalytic material by controlling the amount of PVP added, thereby improving the selectivity for C2 products.
[0011] The present invention drips a potassium borohydride solution into the mixed solution under ice-water bath conditions. The concentration of the potassium borohydride solution in the present invention is 1 mol / L; the mass ratio of the volume of the potassium borohydride solution to polyvinyl pyrrolidone is 20 mL: (0.18-0.22) g.
[0012] In the present invention, after a black precipitate is generated in the solution, stirring is continued for 7 to 9 hours, preferably 7.5 to 8.5 hours.
[0013] The present invention provides a PVP-coated Cu-based electrocatalytic material, which is prepared by the preparation method described in the above technical solution.
[0014] The PVP-coated Cu-based electrocatalytic material provided by the present invention effectively regulates the generation of Cu by incorporating PVP. x+ The intermediate valence state of the CuO2O3 improves the selectivity of the C2 product. At the same time, the PVP coated on the outer layer protects the CuO2O3 x+ Not oxidized to Cu 2+, effectively improving material stability.
[0015] The present invention provides a working electrode for electrocatalytic carbon dioxide reduction, and the preparation raw materials include a PVP-coated Cu-based electrocatalytic material prepared by the preparation method described in the above technical solution.
[0016] In the present invention, the preparation raw materials also include isopropanol and naphthol;
[0017] The mass of the PVP-coated Cu-based electrocatalyst material, the volume of isopropanol and the volume ratio of Nafion are 0.005 g: (450-500) μL: (28-32) μL. In a specific embodiment, the mass of the PVP-coated Cu-based electrocatalyst material, the volume of isopropanol and the volume ratio of Nafion are 0.005 g: 470 μL: 30 μL.
[0018] The present invention uses the above-mentioned electrode to carry out electrocatalytic carbon dioxide reduction, comprising the following steps:
[0019] The working electrode, reference electrode and counter electrode are used as a three-electrode system, 50mL of 0.5mol / L potassium hydroxide solution is used as the electrolyte, CO2 is introduced at a flow rate of 15mL / min, constant potential electrolysis is performed, the voltage range is -1.6V~-2.5V, the time is 2h, and the products such as ethylene, methane, carbon monoxide and hydrogen generated after the reaction starts are sent to gas chromatography for analysis. After the reaction is completed, the liquid in the cathode chamber is taken for nuclear magnetic resonance testing to determine the liquid phase products;
[0020] The working electrode is the working electrode for electrocatalytic carbon dioxide reduction as described in the above technical solution.
[0021] The method for electrocatalytic reduction of carbon dioxide of the present invention can improve the selectivity of C2 products such as ethylene, ethanol, and n-propanol by adopting the PVP-coated Cu-based electrocatalytic material of the above scheme.
[0022] The present invention provides a method for preparing a PVP-coated Cu-based electrocatalytic material, comprising the following steps: mixing cupric chloride dihydrate, polyvinyl pyrrolidone (PVP) and dimethylformamide to obtain a mixed solution; adding a potassium borohydride solution dropwise to the mixed solution under a protective atmosphere and stirring to generate a precipitate, centrifuging, and drying to obtain a PVP-coated Cu-based electrocatalytic material. The present invention introduces PVP, which has the advantages of low price and wide sources. A cross-linked nano-sheet structure copper-based catalytic material is successfully prepared by reducing divalent copper ions with a potassium borohydride solution; 0.2 g PVP (based on 2 mmol copper) is introduced during the reduction process to coat the nano-sheet structure copper, and at the same time, the valence state change of the divalent copper ions during the reduction process is effectively adjusted to control it between monovalent copper and divalent copper, so that it is more conducive to the generation of C2 products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the transmission electron microscope (TEM) image of the copper-based nanomaterial when 0.2 g of PVP is added in Example 1;
[0024] Figure 2 X-ray diffraction pattern of the PVP-coated Cu-based electrocatalytic material prepared in Example 1;
[0025] Figure 3 (a) is a Faraday efficiency diagram of the PVP-coated Cu-based electrocatalytic material prepared in Example 1, and (b) is a Faraday efficiency diagram of the material prepared in Comparative Example 1;
[0026] Figure 4 This is the X-ray photoelectron spectrum of the electrocatalytic material. DETAILED DESCRIPTION
[0027] In order to further illustrate the present invention, a PVP-coated Cu-based electrocatalytic material and a preparation method thereof and an electrode for electrocatalytic carbon dioxide reduction provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0028] Example 1
[0029] 0.2 g of PVP was added to 15 ml of DMF solution and ultrasonicated. After the PVP was dissolved in the DMF solution, 0.324 g (0.2 mmol) of cupric chloride dihydrate was added, and the mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 ml of 1 mol / L potassium borohydride solution was slowly added dropwise, and stirring was continued for 8 hours after a black precipitate was generated in the solution. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 hours to obtain a catalytic material.
[0030] Weigh 0.005 g of the prepared catalytic material, add 470 μL of isopropanol and 30 μL of Nafion, and evenly disperse the material in the solvent, then evenly coat it on the surface of 0.5×1.5 cm carbon paper and dry it at room temperature. The dried carbon paper is used as the working electrode.
[0031] The test system is a three-electrode system of a flow electrolytic cell, consisting of a working electrode, a reference electrode and a counter electrode. The reference electrode is Ag / AgCl (saturated KCl solution), the counter electrode is a commercial platinum sheet, and the working electrode is the prepared carbon paper.
[0032] The electrolyte was 50 mL of 0.5 M / L potassium hydroxide solution, and CO2 was introduced at a flow rate of 15 mL / min. The linear sweep voltammetry (LSV) test was carried out on a CHI 660 electrochemical workstation with a scanning window of -0.6 to -2.5 V. The constant potential electrolysis experiment was carried out on a CHI 660 electrochemical workstation with a voltage setting range of -1.6 V to -2.4 V and a duration of 2 h. After the reaction started, the gas chromatograph was entered and samples were taken every 9 minutes. After the reaction was completed, the liquid in the cathode chamber was taken for nuclear magnetic resonance testing to determine the liquid phase product.
[0033] Figure 1 is a transmission electron microscope (TEM) image of the copper-based nanomaterial, that is, a transmission electron microscope image of the material when 0.2 g of PVP is added in Example 1; Figure 1 It can be seen that anhydrous copper chloride is reduced by potassium borohydride to cross-linked Cu + The nanosheets have a lattice spacing of 0.21 nm. Figure 2 Medium Cu 2 O is consistent. During the reaction, PVP is coated on the surface of Cu with a thickness of 0.1 to 2.5 nm, forming PVP-coated Cu 2 O cross-linked sheet nanomaterials.
[0034] Example 2
[0035] 0.18 g of PVP was added to 15 ml of DMF solution and ultrasonicated. After the PVP was dissolved in the DMF solution, 0.34 g (0.2 mmol) of cupric chloride dihydrate was added. The rest was the same as in Example 1.
[0036] When 0.18g of PVP is added, the copper-based material can be completely coated, and its performance is close to the optimal ratio when 0.2g is added, and the Faraday efficiency of the C2 product is 65.7%.
[0037] Example 3
[0038] 0.22 g of PVP was added to 15 ml of DMF solution and ultrasonicated. After the PVP was dissolved in the DMF solution, 0.34 g (0.2 mmol) of cupric chloride dihydrate was added. The rest was the same as in Example 1.
[0039] When 0.22g of PVP was added, its performance was close to the optimal ratio when 0.2g was added, but there was a slight decrease, and its C2 product Faraday efficiency was 70.8%.
[0040] Comparative Example 1
[0041] 0.1 g of PVP was added to 15 ml of DMF solution and ultrasonicated. After the PVP was dissolved in the DMF solution, 0.34 g (0.2 mmol) of cupric chloride dihydrate was added. The rest was the same as in Example 1.
[0042] The addition of a small amount of PVP (0.1 g) failed to completely cover the copper-based material, making the valence state of the copper-based material closer to that of the material without PVP addition, and had no significant improvement on the C2 product, the Faraday efficiency of the C2 product was 43.3%.
[0043] Comparative Example 2
[0044] 0.3 g of PVP was added to 15 ml of DMF solution and ultrasonicated. After the PVP was dissolved in the DMF solution, 0.34 g (0.2 mmol) of cupric chloride dihydrate was added. The rest was the same as in Example 1.
[0045] The addition of excessive PVP (0.3 g) makes the generated coating layer too thick, which hinders the catalytic efficiency of copper as a catalytic active site, leads to an increase in the competitive reaction for hydrogen evolution, and reduces the selectivity of the C2 product. The Faradaic efficiency of the C2 product is reduced to 58.3%, and the Faradaic efficiency of the competing product hydrogen is increased to 21%.
[0046] Comparative Example 3
[0047] 0.324 g (0.2 mmol) of cupric chloride dihydrate was added to 15 ml of DMF solution and then ultrasonically dissolved; the rest was the same as in Example 1, and the Faraday efficiency of the C2 product was 40.2%. Figure 3 Middle (b).
[0048] Figure 3 (a) is a Faraday efficiency diagram of the PVP-coated Cu-based electrocatalyst material prepared in Example 1, and (b) is a Faraday efficiency diagram of the material prepared in Comparative Example 1. Figure 3 It can be seen that the Faraday efficiency of ethylene is nearly doubled, from 40.2% when PVP is not added to 73.2%, which significantly improves the application of copper-based electrocatalysis in the field of carbon dioxide.
[0049] Figure 4 The X-ray photoelectron spectra of the electrocatalytic materials are shown in Figure 1, wherein (a) is the total X-ray photoelectron spectrum of the material prepared in Example 1; (b) is the Cu2p X-ray photoelectron spectrum of the material prepared in Example 1; (c) is the CuLMN X-ray photoelectron spectrum of the material prepared in Example 1; (d) is the total X-ray photoelectron spectrum of the material prepared in Comparative Example 1; (e) is the Cu2p X-ray photoelectron spectrum of the material prepared in Comparative Example 1; (f) is the Cu LMN X-ray photoelectron spectrum of the material prepared in Comparative Example 1. Figure 4 It can be seen that after adding PVP, the valence state of copper is mainly monovalent copper, such as Figure 4 As shown in (b) and (c); the copper without PVP is all divalent copper, such as Figure 4As shown in (e) and (f), the addition of PVP can effectively ensure that anhydrous copper chloride is reduced to an intermediate valence state that is more conducive to carbon-carbon coupling during the reduction process, thereby effectively improving the selectivity of C2 products.
[0050] As can be seen from the above embodiments, the present invention provides a method for preparing a PVP-coated Cu-based electrocatalytic material, comprising the following steps: mixing cupric chloride dihydrate, polyvinyl pyrrolidone (PVP) and dimethylformamide to obtain a mixed solution; under a protective atmosphere, potassium borohydride solution is added dropwise to the mixed solution under stirring to generate a precipitate, centrifuged, and dried to obtain a PVP-coated Cu-based electrocatalytic material. The present invention introduces PVP (polyvinyl pyrrolidone), which has the advantages of low price and wide sources. A cross-linked nano-sheet structure copper-based catalytic material is successfully prepared by reducing divalent copper ions with potassium borohydride solution; (0.18-0.22 g) of high molecular polymer PVP (based on 2 mmol copper) is introduced during the reduction process to coat the nano-sheet structure copper, and at the same time, the valence state change of divalent copper ions during the reduction process is effectively adjusted, and it is controlled between monovalent copper and divalent copper, so that it is more conducive to the generation of C2 products. The experimental results show that the Faraday efficiency of the PVP-coated Cu-based electrocatalyst material is 73.2%, which is nearly doubled compared to undoped PVP.
[0051] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a PVP-coated Cu-based electrocatalytic material, comprising the following steps: Mixing cupric chloride dihydrate, polyvinyl pyrrolidone and dimethylformamide to obtain a mixed solution; Under a protective atmosphere, a potassium borohydride solution is added dropwise to the mixed solution under stirring to generate a precipitate, which is then centrifuged and dried to obtain a PVP-coated Cu-based electrocatalytic material.
2. The preparation method according to claim 1, characterized in that: The volume ratio of the mass of the cupric chloride dihydrate, the mass of polyvinyl pyrrolidone and dimethylformamide is 0.34 g: (0.18-0.22) g: (14-16) mL.
3. The preparation method according to claim 1, characterized in that: To the mixed solution was added dropwise potassium borohydride solution under ice-water bath condition.
4. The preparation method according to claim 1, characterized in that: The concentration of potassium borohydride solution is 1 mol / L; The volume ratio of the potassium borohydride solution to the mass ratio of polyvinyl pyrrolidone is 20 mL: (0.18-0.22) g.
5. The preparation method according to claim 1, characterized in that: After the precipitate is formed, stirring is continued for 7 to 9 hours to allow potassium borohydride to react completely with Cu and PVP.
6. A PVP-coated Cu-based electrocatalytic material prepared by the preparation method according to any one of claims 1 to 5.
7. A working electrode for electrocatalytic reduction of carbon dioxide, wherein the raw material for preparation comprises a PVP-coated Cu-based electrocatalytic material prepared by the preparation method according to any one of claims 1 to 5.
8. The electrode for electrocatalytic carbon dioxide reduction according to claim 7, characterized in that: The raw materials for the preparation also include isopropyl alcohol and naphthol; The mass of the PVP-coated Cu-based electrocatalytic material, the volume of isopropanol and the volume ratio of naphthol are 0.005 g: (450-500) μL: (28-32) μL.
Citation Information
Patent Citations
Method for preparing nano Ag / PVP (polyvinyl pyrolidone) composite material by utilizing ultraviolet irradiation
CN102532376A
Multivalent copper nano-material, preparation method thereof and application of multivalent copper nano-material as electrocatalyst in carbon capture technology
CN113862715A
Catalyst for preparing ethanol by electrically reducing CO and preparation method of catalyst
CN114318378A
Octahedral Cu2O / CuO heterojunction catalyst as well as preparation method and application thereof
CN115821319A
Preparation method of CuO-coated Cu2O composite catalyst for electrocatalytic reduction of carbon dioxide into ethylene
CN116288474A